(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Field experiments were conducted at the Central Research Station of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during the period from November to February in 2004-05 and 2005-06 to evaluate the effect of different levels of sulphur (0, 20, 40, 60, and 80 kg/ha) on rapeseed variety BARI Sarisha-15. Results showed that the most of the growth parameters and yield attributes were significantly influenced by different doses of sulphur. The growth parameters, yield and yield contributing characters were increased with the increasing levels of sulphur fertilizer up to 60 kg S/ha and with the doses beyond that were found to decrease. All growth parameters like plant height, leaf area, dry matter accumulation, leaf area index, crop growth rate, net assimilation rate, and relative growth rate and all yield components, such as number of siliquae per plant, seeds per siliqua, 1000-seed weight and seed yield per plant were found maximum from the treatment with 60 kg S/ha, which was at par with 80 kg S/ha. The highest seed yield (1990 and 1896 kg/ha) were found when S was used @ 60 kg/ha. The same treatment gave 24.71 % and 24.32 % higher seed yield than the control treatment, which were statistically identical with dose at 80 kg /ha of sulphur in both the years. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14389 Bangladesh J. Agril. Res. 37(4): 645-652, December 2012